Global research neglect of population-based approaches to smoking cessation: time for a more rigorous science of population health interventions - Lawrence, David; Mitrou, F.; Zubrick, Stephen (Wiley-Blackwell Publishing Ltd., 2011)
ABSTRACTIt has been argued that the preponderance of studies into individual smoking cessation therapies seems grossly out of proportion to the number of people who use these therapies to quit smoking, and that this imbalance is due to factors such as the role of the pharmaceutical industry in funding research and a general bias towards individual- rather than population-based approaches to medical and health problems. We believe that there are other significant factors that affect the balance of research in smoking cessation, such as the higher standards of evidence required to justify the implementation of individual medical therapies compared with population-based interventions. We argue that research practitioners in the area of population tobacco control are well placed to address this imbalance by setting more rigorous standards of evidence for population health interventions. This could be achieved by setting aside a small proportion of funds from population health and advocacy activities to invest in studying their effectiveness. We believe that this would potentially return information of sufficient value to justify increasing overall population investment beyond the cost of the additional research component. Additional benefits would be gained from increased research in this area, such as better understanding of how to translate tobacco control initiatives to developing countries with high smoking rates, and how to target disadvantaged and marginalized populations more effectively in developed countries that continue to have high rates of smoking and low rates of smoking cessation, despite the existence of broad population-based strategies.